Pricing decisions of online and offline retailers, each offering a competing benefit - Yael Perlman (Operations Research Perspectives, 2022)
This paper studies a duopolistic market consisting of a conventional offline retailer and an online retailer, each of whom offers a competing benefit (attribute): Specifically, the conventional retailer is superior in terms of social aspects of the shopping experience, such as helpfulness of salespeople, whereas the online retailer offers the possibility of rapid and convenient procurement. Importantly, customers are assumed to be heterogeneous in the extent to which they value each attribute. We first study a scenario of a fully-covered market, in which consumers' valuations of the attributes are high enough that every consumer purchases a product from one of the channels. In this case, we derive closed-form expressions for the retailers' pricing strategies, their expected profits, and their market shares. We find that, surprisingly, under some conditions, the online retailer's price is higher than the conventional retailer's, despite the lower costs incurred by the former. Next, we study the realistic scenario in which the market is not fully covered (i.e., consumers have the option to avoid purchasing altogether), and compare it with the fully-covered market scenario. Specifically, we identify conditions under which, at equilibrium, each consumer buys a product, regardless of consumers' valuations of the attributes.
Keywords: 650; Consumer choice; Game theory; Internet/offline retailing; Pricing competition